Bankruptcy Model Analysis: Comparative Studies Between Sharia and Non Sharia Manufacturing Companies - Ruhadi, Ruhadi; Mai, Muhammad Umar (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
This study aims to find out three important things: first is based on the analysis of three bankruptcy models that Altman, Springate and Zmijewsky, which is the most accurate in predicting the potential bankruptcy of sharia and non sharia, secondly based on the most accurate model, whether sharia companies have a potential bankruptcy smaller than non_sharia. The third is to identify what is the most influential factors to the potential bankcruptcy for both sharia and non sharia companies. Trought the number of 458 unit observations of manufacturing companies and studies performed using Mean Square Error (MSE) and analysis of variance, it was found that the most accurate model in predicting potential bankruptcy is Altman Z_score. Based on this model could be found, statistically significant that a group of sharia has a potential bankruptcy smaller than the non_sharia. Based on the third question, could be found that good corporate governance have positive and significant effect to potential bankcruptcy for the sharia companies, while the rate exchange of rupiah to US dollar has negative and significant effect to ones. Other finding that the only institutional ownwership factor that have positif and significant effect to the potential bankcruptcy of the non sharia companies.DOI: 10.15408/aiq.v9i2.4466